Proses Pembuatan Tepung Pempek - A.D. Murtado; Ade Vera Yani (Jurnal Pangan dan Gizi, 2023)
Pempek is known as a food originating from the city of Palembang which is made from a mixture of ground fish and tapioca flour. Pempek which is made from snakehead fish is the most popular pempek in the community because it doesn't smell fishy. . Pempek can be found in big cities in Indonesia, especially Jakarta, although the taste is not as delicious as in Palembang. This is due to the limited availability of fresh ground fish, especially snakehead fish. The research aims to make pempek flour as an ingredient for pempek, so that making pempek becomes easier and simpler. The method used is the experimental method, trying several ways of making pempek flour. The treatments applied were: a) variations in the ratio of ground fish and tapioca, namely 1:08 (R1), 1:1 (R2), 1:1.2 (R3), 1:1.4 (R4), 1:1.6 (R5), 1 :1.8 (R6), 1:2 (R7), b) variations in the mixing method (dry and wet), and c) variations in drying temperature, namely: 35oC (T1), 40oC (T2), 45oC (T3), 50oC ( T4), 55oC (T5) and 60oC (T6). Parameters measured were the yield, odor and degree of whiteness of pempek flour. It was found that the use of tapioca and ground fish ingredients with a ratio of 1:1.6 which were processed with stirring at a speed of 3000rpm and using a drying temperature of 40oC for 8 hours, produced the best pempek flour, produced pempek flour which was preferred by the panelists with a yield of 76.92% and a degree of whiteness of 89.70%.